The significance of meaning-making, agency and social support: a narrative study of how poor women cope with perinatal loss - Sturrock, Colleen (Department of Psychology, 2015)
Perinatal loss (stillbirth or the death of a neonate) can result in considerable psycho-social disruption for mothers. As women grieve, they try to make meaning of the death of their baby. In contexts of social and economic deprivation, perinatal loss often occurs alongside other difficulties which may affect and limit women's ability to make meaning. A narrative approach was used to explore how meaning-making functions in such contexts. In-depth interviews were conducted with 15 women who had experienced perinatal loss while attending a state maternity hospital. Narratives which the mothers constructed of the event were examined in order to understand what meanings they derived from the loss, and how these were (or not) achieved. These narratives were often linked to other stories of pervasive life difficulties. Despite their difficult contexts, the bereaved mothers engaged in meaning-making in similar ways to those described in previous studies in more affluent settings: they attempted to integrate the loss with their identity and goals, they affirmed the baby as a real person to be mourned and they searched for reasons for the loss. The effect of their contexts on meaning-making was mediated by social support and personal agency. Where one or both of these were present, the bereaved mothers were able to find meaning in their loss; women who had neither seemed unable to do so. Those who portrayed themselves as agentic were able to reflect on their experience and make decisions to change their lives. Mothers with strong social support made meaning through conversations, social validation of the loss and social help which mitigated against the sense of helplessness engendered by their loss and circumstances. It is recommended that hospital and counselling services implement practices which help to build or consolidate personal agency and social support to facilitate successful meaning-making following perinatal loss.